MEDICAL MALPRACTICE. THE MALPRACTICE INSURANCE - Ruxandra-Cristina DUȚESCU (Challenges of the Knowledge Society)
Increasingly, complaints about medical malpractice ocure extreme situations such as the death of the person or the occurrence of irreparable injuries. Professional misconduct in the exercise of the medical or medical-pharmaceutical act generating harm to the patient implies the civil liability of medical personnel and the provider of medical, sanitary and pharmaceutical products and services. Law no. 95/2006 on the health reform stipulates the obligation of the medical staff to conclude a malpractice insurance for the cases of professional civil liability for the damages created by the medical act, the indemnities being the responsibility of the insurer, within the limits of the liability established by the insurance policy.